Exploring the practical issues and use of modern power, control and sensing circuitries of a 6/4-pole switched reluctance motor drive. (5th April 2007) - Paramasivam, Shanmugam; Arumugam, R.
This paper explores practical issues and use of modern power, control and sensing circuitries of a 6/4-pole Switched Reluctance Motor (SRM) drive. A DSP-based SRM drive system consists of classic bridge converter including power MOSFETs and their gate drivers, freewheeling diodes, sensing circuit, DSP controller and a SRM that is being controlled by the controller. Few logic components are also required that will interface with the DSP for communication. The complete practical issues experienced with modern power, control and sensing circuitries of a 6/4-pole SRM drive is presented.